Microcomputer-based langmuir probe system - Wong, C.S.; Saw, S.H.; Chin, Oi Hoong (1985)
A simple microcomputer-basedd ata acquisition systemi s set up to obtain the I-V characteristic of the Langmuir probe. The system is ideal for extensive probe data collection in the study of steadystate plasmas. The Langmuir probe is a simple but effective tool for the diagnostic of fairly large volume, relatively cold and low density plasmas.F rom the I-V .characteristico f the probe, plasmap arameters such ag the electron temperature, electron density, space potential and electron energy distribution can be deduced. For a time-varying plasma, the pulsed Langmuir probera must be used. In the case of a steady-state plasma, it is usually sufficient to use the point-by-point technique, although the pulsed method can also be employed. However, the process of obtaining the Langmuir probe characteristic by the point-by-point method and its analysis is tedious and time-consuming if it is done manually. This is particularly true in casesw here the Langmuir probe is employeda s a basicd iagnostic and extensived ata are required to be collectedc oncurrently with other diagnosticso f the plasma. In this note, a simple microcomputer-basedd ata acquisition systemf or the Langmuir probe is described. The system employs an Apple-II microcomputer to control the variation of the probe's bias potential as well as to monitor the probe curent automatically. The data acquisition system consists of a 64k RAM Apple-II micrommputer which is supported by a high-resolution CRT display unit; two mini floppy diskdrives and a dot matrix printer with highresolution graphic capability (Fig. l). Data acquisition is done via a multi-channel A/D + D/A interface card (Mountain Computer Inc.) which can be plugged directly into the expansion slot of the Apple-II. This interface card provides 16 cannelse ach of analog-todigital and digital-to-analogc onverters.T he rangeo f its analogi nput/output level is -5V to +5V, with a digital equivalenceo f 0 to 255. The experimentasl et-upo f the miqocomputer-basedo uble Langmuirp robe measuremenotf a plasma is as shown in Fig. 2. A I kO resistor is connected in place of the usual microammeter for measuringth e probe curent, Ip. The potentiald rop acrosst he I kS2r esisteri s expectedt o be of the order of mV only and hence it must be amplified before it is fed into an A/D channel of the computer. This is done by using a HP2470A data amplifier. The probe potential Vp is supplied by using the HP457A power amplifier acting as a variable power supply. The output of the power amplifier can be varied within the range of -3OV to +30V by applying a voltage of -3V to +3V to its input. Thus when used in conjunction with a digitaltoanalog converter, the HP467A power amplifier functions as a low voltage digitally controlled power supply. This iurangementis good enoughf or the presentp urpose.I f -higherv oltagesa re required, the digitally controlled power supply described by Fanelli and Merangelli" may be employed.